Dermatitis due to straw itch mite in Assam - Nath Reema; Saikia Lahari; Choudhury M; Mahanta J (Wolters Kluwer Medknow Publications, 2007)
Mites belonging to Pyemotidae family are an important cause of human dermatoses. Though their bites are painless, yet, afterwards severe itching and possible secondary infection. Most of the time mites could not be demonstrated from the lesion. We are presenting a case where mites could be seen in scrapping from a typical lesion in man.